The Enlightened Path: Muḥammad ‘Abduh's Fusion of Reason and Revelation - Gilang Febiyanto, Aditiya; Najib Azka, Andhika (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
This research paper, titled